Impact of Reflexology on Menopause among Post menopausal Women - Oke, Avani; Sathe, Reena (Journal of Neonatal Surgery, 2025)
Menopause is known as the termination of fertility in women due to aging and is a part of women normal developmental and biological process. The article discussed about Impact of Reflexology on Menopause among Post menopausal Women. Menopause develop hot flushes, insomnia and also causes anxiety. The study revealed that relaxation and diversion help reducing the effect of Menopause. The study showed that foot reflexology had a positive impact in reducing the menopausal symptoms.